Exercise training‐induced improvement in skeletal muscle PGC‐1α‐mediated fat metabolism is independent of dietary glycemic index - Mulya, Anny; Haus, Jacob M.; Solomon, Thomas P.J.; Kelly, Karen R.; Malin, Steven K.; Rocco, Michael; Barkoukis, Hope; Kirwan, John P. (Obesity (Silver Spring, Md.), 2017)
Objective This study hypothesized that a low‐glycemic diet combined with exercise would increase expression of nuclear regulators of fat transport and oxidation in insulin‐resistant skeletal muscle. Method Nineteen subjects (64 ± 1 y; 34 ± 1 kg/m2) were randomized to receive isocaloric high‐glycemic‐index (HiGIX; 80 ± 0.6 units, n = 10) or low‐glycemic‐index (LoGIX; 40 ± 0.3 units, n = 9) diets combined with supervised exercise (1 h/d, 5 d/wk at ∼85% HRmax) for 12 weeks. Insulin sensitivity was determined by hyperinsulinemic‐euglycemic clamp. Skeletal muscle biopsies were obtained before and after the intervention to assess fasting gene and protein expression. Results Weight loss was similar for both groups (9.5 ± 1.3 kg). Likewise, improvements in insulin sensitivity (P < 0.002) and PPARγ (P < 0.002), PGC‐1α (P = 0.003), CD36 (P = 0.003), FABP3 (mRNA, P = 0.01 and protein, P = 0.02), and CPT1B (mRNA, P = 0.03 and protein, P = 0.008) expression were similar for both interventions. Increased insulin sensitivity correlated with increased PGC‐1α expression (P = 0.04), and increased fasting fat oxidation correlated with increased FABP3 (P = 0.04) and CPT1B (P = 0.05) expression. Conclusions An exercise/diet program resulting in 8% to 10% weight loss improved insulin sensitivity and key molecular mechanisms in skeletal muscle that are controlled by PGC‐1α. These effects were independent of the glycemic index of the diets.